Decreased neuronal excitability in hypertriglyceridemia hamsters with acute seizures - Shen, Qiuyue; Liu, Nana; Jiang, Yuwu; Liu, Lili; Hou, Xinlin (Frontiers in Neurology, 2024)
IntroductionNeonatal seizures are the most common clinical manifestation of neurological dysfunction in newborns, with an incidence ranging from 1 to 5‰. However, the therapeutic efficacy of current pharmacological treatments remains suboptimal. This study aims to utilize genetically modified hamsters with hypertriglyceridaemia (HTG) to investigate the effects of elevated triglycerides on neuronal excitability and to elucidate the underlying mechanisms. The ultimate goal is to identify novel therapeutic targets for the treatment of neonatal seizures.MethodsAcute seizure models were established both in vivo and ex vivo using wild-type and Apolipoprotein C2 knockout (Apoc2−/−) hamsters. The frequency of tonic–clonic seizures was recorded. Excitatory postsynaptic potentials (EPSPs) and evoked action potentials (eAPs) of pyramidal neurons in the frontal cortex were measured. Fatty acid metabolomic analysis was conducted on microdialysate from the frontal cortex tissue post-seizure, and mRNA expression changes were also assessed.ResultsApoc2−/− hamsters exhibited a reduced frequency of tonic–clonic seizures and diminished EPSP and eAP in comparison to wild-type hamsters. Following seizure induction, free palmitic acid levels in the frontal cortex dialysate significantly decreased, while the expression of palmitoyl acyltransferase 14 (ZDHHC14) in the frontal cortex tissue was higher in Apoc2−/− hamsters than in wild-type hamsters. Additionally, the amplitude of transient outward potassium currents (IA) in cortical neurons of Apoc2−/− hamsters was observed to be elevated compared to wild-type hamsters.ConclusionHypertriglyceridemic Apoc2−/− hamsters exhibited reduced seizure frequency and decreased cortical neuron excitability. The upregulation of ZDHHC14, leading to increased IA, may be a crucial mechanism underlying the observed seizure protection.